Nutrition and the Function of the Central Nervous System - Billy R. Hammond (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Neuroscience, as a field, has only recently expanded to consider how the nervous system might be influenced by interaction with other bodily systems. The psychology curriculum never, for instance, included courses on nutrition. Although we learn about the body as if it is segregated into systems (cardiovascular, immune, digestive, etc.), these systems are not truly separate. If the aphorism, you are what you eat, is literally true: then you—your personality, thoughts, feelings, etc.—are, at least partly, a product of your diet. Such recognitions have spawned the new subdiscipline, nutritional neuroscience: the study of the role of diet on neurochemistry, neurobiology, cognition and behavior. This collection explores this exciting new area.